2018
DOI: 10.3390/nu10010031
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Plasma Free Palmitoleic and Dihomo-Gamma Linoleic Fatty Acids Are Higher in Children with Abdominal Obesity

Abstract: Increased plasma free fatty acids (FFAs) are associated with cardiometabolic risk factors in adults with abdominal obesity (AO). However, this association remains controversial in children. This study analyzed plasma FFA concentration in children with and without AO. Twenty-nine children classified with AO were matched by age and sex with 29 non-obese individuals. Blood samples were collected after fasting for 10–12 h. Plasma concentration of glucose, insulin, triglycerides, total cholesterol, low-density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
2
18
0
1
Order By: Relevance
“…Interestingly, this finding is in line with recently reported data suggesting that elevated total serum ceramide, as well as specific concentrations of myristic, palmitic, palmitoleic, stearic, oleic, behenic and lignoceric ceramide, with insulin resistance and play a potential role in the development of NAFLD in obese children [46]. The correlation of the lipid profile with glucose and insulin levels has been reported to probably mirror a still preserved ability to adapt to a caloric challenge compared with metabolically unhealthy individuals [47,48], in line with recent suggestions that propose a fatty acid profile is a useful tool to explain part of the heterogeneity between abdominal obesity and MetS [11,48,49]. Others have reported that, in addition to palmitic and stearic acid, other FAs are deranged and that increased activity of C16 Δ9-desaturase and C18 Δ9-desaturase in parallel with decreased Δ5-desaturase activity may be a causative factor in disturbed fatty acid metabolism [50].…”
Section: Discussionmentioning
confidence: 76%
“…Interestingly, this finding is in line with recently reported data suggesting that elevated total serum ceramide, as well as specific concentrations of myristic, palmitic, palmitoleic, stearic, oleic, behenic and lignoceric ceramide, with insulin resistance and play a potential role in the development of NAFLD in obese children [46]. The correlation of the lipid profile with glucose and insulin levels has been reported to probably mirror a still preserved ability to adapt to a caloric challenge compared with metabolically unhealthy individuals [47,48], in line with recent suggestions that propose a fatty acid profile is a useful tool to explain part of the heterogeneity between abdominal obesity and MetS [11,48,49]. Others have reported that, in addition to palmitic and stearic acid, other FAs are deranged and that increased activity of C16 Δ9-desaturase and C18 Δ9-desaturase in parallel with decreased Δ5-desaturase activity may be a causative factor in disturbed fatty acid metabolism [50].…”
Section: Discussionmentioning
confidence: 76%
“…Increased cardiovascular risk and the early-onset of chronic diseases are among the health consequences of childhood obesity [4,5]. It has been recognized that evaluating weight status by traditional tools such as body mass index (BMI) to screen for cardio-metabolic risks is limited by the fact that BMI does not reflect fat distribution [6]; for instance, accumulation of visceral fat (intra-abdominal obesity), compared to subcutaneous fat (peripheral), has been associated with a greater cardiovascular risk [7,8,9,10] and metabolic disorders such as high blood pressure, dyslipidemia, and altered glucose metabolism [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Combinatorial effects of fatty acids according to their relative abundance in the tissue of HFD-fed mice need to be considered in the future. Interestingly, adipose tissue palmitoleic acid content normally declines during childhood and two studies found a positive correlation between circulating free palmitoleic acid and abdominal obesity in children [38], [49], [50]. Palmitoleic acid has been demonstrated to act as an endocrine signal but further studies are required to determine the signaling mechanisms and the impact of excess dietary supply on early fat expansion [38].…”
Section: Discussionmentioning
confidence: 99%